Hubungan Sikap dan Dukungan Keluarga dengan Kunjungan Ibu Nifas Di Wilayah Kerja Puskesmas Kombeng Tahun 2026 - Norifa Ifan; Chandra Sulistyorini; Sucita Tripertiwi; Dwi Hartati (Poltekkes Kemenkes Kupang, 2026)
Background: Postnatal care (PNC) is an essential effort to detect early danger signs during the postpartum period. Physiologically, the puerperium lasts for 42 days (6 weeks) after delivery; therefore, postpartum visits should ideally be conducted in accordance with health service standards within this period. The coverage of postpartum visits in the working area of the Kombeng Public Health Center showed a decline from 2024 to 2025, from 82.1% to 71.4% (a decrease of 10.7%), which is suspected to be related to maternal attitudes and family support regarding the importance of postpartum examinations. Objectives: This study aimed to determine the relationship between attitude and family support with postpartum visits among mothers. Methods: The study employed a quantitative method with an analytic descriptive design and a cross-sectional approach. The population consisted of all postpartum mothers during the 42-day postpartum period in January–February 2026, with a total sample of 38 respondents using a total sampling technique. Data were collected using questionnaires and maternal and child health (MCH) books/medical records, and analyzed using the Fisher’s Exact Test. Results: The results showed that most mothers had a positive attitude (63.2%), received family support (73.7%), and completed postpartum visits (73.7%). There was a significant relationship between attitude and postpartum visits (p = 0.002), as well as between family support and postpartum visits (p = 0.01). Conclusions: Conceptually, a less supportive maternal attitude toward postpartum visits is generally characterized by the perception that examinations are not necessary in the absence of complaints, whereas a positive attitude is reflected in the awareness that the postpartum period is a vulnerable phase requiring health monitoring. These findings indicate that psychosocial factors play a role in compliance with postpartum visits; therefore, improving education and involving families are essential to optimize postpartum visit coverage for the early detection of maternal health problems.